Slovak Republic : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2007 Article IV Consultation highlights the Slovak Republic's macroeconomic outlook and policy discussions. The National Bank of Slovakia (NBS) has been following a hybrid monetary framework focused on restraining inflation and on maintaining the exchange rate within the Exchange Rate Mechanism 2 (ERM2) requirements. Executive Directors encouraged the NBS to conduct its policy, and its communications with market participants. They also stressed the importance of ensuring that the labor code amendments under consideration would not raise labor costs and reduce labor market flexibility.